Role of global deoxyribonucleic acid methylation and molecular hypoxia changes in male infertility - Zainab Abdul Jabbar; Rakad Mohammed Khamas AL-Jumaily (Universa Medicina, 2026)
Infertility is recognized as a major global health issue and has become one of the primary challenges in reproductive health; its prevalence and incidence are steadily increasing worldwide. Recent research has highlighted the critical role of epigenetic dysregulation as a direct factor affecting male infertility. The objective of this review is to investigate the relationship between epigenetic modifications (specifically 5-methylcytosine and 5-hydroxymethylcytosine) and essential male reproductive outcomes, including the spermatogenesis process, testicular function, and semen quality parameters. Furthermore, this study explores the influence of micronutrients such as vitamin B12, homocysteine metabolism, and antioxidant capacity on DNA methylation and genomic stability. Significantly, this review establishes a novel link between infertility and cellular hypoxia focusing on the modulation of hypoxia-inducible factor (HIF-1α and HIF-2α) as a potential therapeutic strategy. Additionally, this work introduces the overlooked association between HIF-2α and infertility, offering novel insights since current findings regarding HIF-2α in male infertility are remarkably limited. A literature search was conducted on PubMed, ScienceDirect, Springer Link, Oxford Academic and Nature databases for sources published in English from 2015 to 2025, using the following keywords: male infertility, DNA methylation, hypoxia, HIF-1α, and immunity. Our work investigates the interruption of inflammatory cytokines and immunological markers by linking them with molecular factors, micronutrients and hypoxia pathways. This approach provides an integrated foundation for advanced diagnostic and therapeutic strategies. Ultimately, understanding these molecular signatures provides ways to enhance reproductive outcomes and improve success rates of assisted reproductive techniques.